Information literacy of a university teacher as an important condition for an anti-plagiarism test - Vitaliy Gennadevich Svechkaryov; Tatyana Alexandrovna Ivaschenko; Larisa Kazbekovna Belous (Вестник Майкопского государственного технологического университета, 2023)
The relevance of the research is associated with the rapid development of the Internet and information technologies. This fact has greatly simplified the ability to access a variety of information resources. Along with the huge positive impact of this phenomenon on the development of modern society, serious problems have arisen related to the unfair use of information [6]. In particular, this is the illegal attribution of authorship to another's work or incorrect borrowing of a part of it (the so-called plagiarism problem) [12]. This phenomenon is especially widespread among students. Among students such a method of writing works as copying materials from the Internet with minimal editing is common. Currently, teachers are actively using online services to verify the uniqueness of the work. These are text borrow detection systems that easily block work due to low originality. To increase the “originality” of the work, some students use the anti-plagiarism-killer program (a program to hide the detection of text borrowings). There are services offering to make the text 75-99 per cent “original” [4]. A search for information on this issue revealed a lack of modern specialized literature and relevant knowledge among university teachers. Thus, the development of modern technologies for detecting traces of programs to hide the detection of text borrowings seems to be very relevant. The purpose of the research is to identify the capabilities of the anti-plagiarism-killer program to level the operation of the “Anti-plagiarism.vuz” system, to develop a technology for identifying jobs that have been processed by the anti-plagiarism killer program. The research methods used are analysis of the problem situation, methods of the theory of information retrieval, information processing and pattern recognition. The results and key findings: the article describes the most common technical methods of circumventing the anti-plagiarism system and methods for their detection. The material was prepared on the example of the popular text editor Microsoft Word and the most popular online anti-plagiarism. Vuz. service. Key conclusions about the imperfection of the anti-plagiarism.vuz online service have been made, the need for its further improvement and the warning against the use of anti-plagiarism-killer programs have been noted. The need has been identified to constantly improve information culture and deepen knowledge in the field of information technology by university teachers.